2020
DOI: 10.1111/1475-6773.13585
|View full text |Cite
|
Sign up to set email alerts
|

Are health systems redesigning how health care is delivered?

Abstract: Objective To explore why and how health systems are engaging in care delivery redesign (CDR)—defined as the variety of tools and organizational change processes health systems use to pursue the Triple Aim. Study Setting A purposive sample of 24 health systems across 4 states as part of the Agency for Healthcare Research and Quality's Comparative Health System Performance Initiative. Study Design An exploratory qualitative study design to gain an “on the ground” understanding of health systems’ motivations for,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Hospital systems have often said that their mergers and acquisitions—which have accelerated in recent years 1,14,16,46,47 —are associated with higher quality due to improved care coordination and economies of scale 1–7 . Prior literature has suggested that, despite evidence of variation in surgical outcomes within highly rated hospital systems, 10 many, if not most, patients expect hospitals from the same system to offer the same standard of care, regardless of whether they are at a flagship hospital or its local affiliate 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital systems have often said that their mergers and acquisitions—which have accelerated in recent years 1,14,16,46,47 —are associated with higher quality due to improved care coordination and economies of scale 1–7 . Prior literature has suggested that, despite evidence of variation in surgical outcomes within highly rated hospital systems, 10 many, if not most, patients expect hospitals from the same system to offer the same standard of care, regardless of whether they are at a flagship hospital or its local affiliate 8 …”
Section: Discussionmentioning
confidence: 99%
“…Hospital systems have often said that their mergers and acquisitions-which have accelerated in recent years 1,14,16,46,47 are associated with higher quality due to improved care coordination and economies of scale. [1][2][3][4][5][6][7] Prior literature has suggested that, despite evidence of variation in surgical outcomes within highly rated hospital systems, 10 many, if not most, patients expect hospitals from the same system to offer the same standard of care, regardless of whether they are at a flagship hospital or its local affiliate. 8 To study this, we performed a large, carefully matched study across 35 of the largest HRRs, controlling for 32 general surgical procedures, 55 comorbidities and functional status indicators, multimorbidity status, emergent admission status, and sociodemographic variables including age, sex, race, dual-eligibility, and neighborhood education and poverty levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation